Women's Monasticism and Medieval Society : Nunneries in France and England, 890-1215 - Venarde, Bruce L., 1962- (Book collections on Project MUSE., 1997)
"In this innovative and engaging work, Bruce L. Venarde uncovers a largely unknown story of women's religious lives and puts female monasticism in the mainstream of medieval ecclesiastical history. Venarde deftly interweaves narrative and statistical data to describe in broad historical context the multiplication of French and English nunneries during the central Middle Ages."--Jacket